The Development of Learning Organizations in Private Schools in the Lower Northern Region 2 of Thailand : - - Pasomtong , Ranee; Dararuang, Kritsana; Kongyoungyune, Rungradit (Journal of Dhamma for Life, 2026)
This study investigates the causal relationships among leadership factors, organizational climate, and the learning organization status of private basic education schools in the Lower Northern region 2 of Thailand. The objectives are to examine the levels of transformational leadership, organizational climate, and learning organization attributes; to analyze their interrelationships; and to assess the influence of leadership and climate on organizational learning development. A sample of 355 private school teachers from four provinces Kamphaeng Phet, Phichit, Nakhon Sawan, and Uthai Thani was selected using multi-stage random sampling. Data were collected via a validated and reliable questionnaire and analyzed using descriptive statistics, Pearson correlation, and stepwise multiple regression analyses. Findings reveal that all three constructs leadership, organizational climate, and the learning organization are rated at very high levels. Notably, transformational leadership dimensions of vision and inspiration, along with organizational climate dimensions of responsibility, warmth and support, and clear organizational structure, are predominant. Within the learning organization, knowledge management and team learning play critical roles. Significant positive correlations exist among leadership, organizational climate, and learning organization variables. Key predictors influencing the learning organization include organizational commitment, organizational structure, work standards and expectations, inspirational leadership, supportive climate, intellectual stimulation, and idealized influence, which together account for 90.1% of the variance in learning organization capability. Based on these findings, the study proposes actionable strategies to develop transformational leadership, foster a learning-conducive organizational climate, and enhance internal components of the learning organization through effective knowledge management, teamwork, and appropriate use of information technology. These approaches aim to promote sustainable and effective learning organizations within private schools in the Lower Northern region 2 of Thailand.